Chinese as a Second Language Research (De Gruyter Mouton, 2012)
The CASLAR journal provides a forum for scholars interested in Chinese as a Second Language research and focuses on research on the acquisition, development and use of CSL. It supports interaction and scholarly debate between researchers representing different subfields of linguistics with a focus on CSL, and serves as a forum for researchers who are looking for new tools and methods to investigate and better understand CSL.